2019
DOI: 10.1016/j.tranon.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

miR-224 Is Significantly Upregulated and Targets Caspase-3 and Caspase-7 During Colorectal Carcinogenesis

Abstract: miR-224 has recently emerged as a driver oncomiR in sporadic colorectal carcinogenesis, but its pathogenetic role is still controversial. A large phenotypical and molecularly characterized series of preinvasive and invasive colorectal lesions was investigated for miR-224 expression by qRT-PCR and in situ hybridization. The caspase-3 and caspase-7 status was also assessed and correlated to miR-224 dysregulation. miR-224 was significantly upregulated during the adenoma-carcinoma sequence and in the context of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…We observed hypermethylation at these CpG loci and increased miR-224/miR-452 expression in ER-compared to ER + tumors. Studies have reported both up-and down-regulation of miR-224 in various cancers, suggesting its cell type-speci c expression and function (43)(44)(45). Speci cally, in breast cancer, and consistent with our study, one study reported increased miR-224 expression in both triple negative breast cancer cell lines and tumor tissues, and that its knockdown in aggressive triple negative breast cancer cells reduced proliferation, migration and invasion (46).…”
Section: Discussionsupporting
confidence: 90%
“…We observed hypermethylation at these CpG loci and increased miR-224/miR-452 expression in ER-compared to ER + tumors. Studies have reported both up-and down-regulation of miR-224 in various cancers, suggesting its cell type-speci c expression and function (43)(44)(45). Speci cally, in breast cancer, and consistent with our study, one study reported increased miR-224 expression in both triple negative breast cancer cell lines and tumor tissues, and that its knockdown in aggressive triple negative breast cancer cells reduced proliferation, migration and invasion (46).…”
Section: Discussionsupporting
confidence: 90%
“…We observed hypermethylation at these CpG loci and increased miR-224/miR-452 expression in ER- compared to ER+ tumors. Studies have reported both up- and down-regulation of miR-224 in various cancers, suggesting its cell type-specific expression and function [ 43 45 ]. Specifically, in breast cancer, and consistent with our study, one study reported increased miR-224 expression in both triple negative breast cancer cell lines and tumor tissues, and that its knockdown in aggressive triple negative breast cancer cells reduced proliferation, migration and invasion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several lines of evidence have demonstrated miR-592 may participate in CRC tumorigenesis ( 37 , 38 ) and metastasis ( 39 , 40 ). Furthermore, a study identified a potential role for miR-224 in CRC progression ( 41 ). Finally, high expression levels miR-224 have been associated with worse survival of patients in CRC ( 42 ).…”
Section: Discussionmentioning
confidence: 99%